Selection of panelists for a Delphi survey on emergency preparedness and management - Kimmo Laakso (USA, 2022)
In emergency situations a group of individuals representing different organizations, for example authorities and companies, have to work together. They have to absorb a large amount of information about the disaster over a short period of time. In order to be able to make the right decisions, individuals need to understand each other even though they may be from different lines of business. In our research, the target is to stress the importance of a common language in emergency management. Our plan is to gather a group of experts to communicate with the Delphi method on possible differences in the terminology used in different lines of business. Experts from the authorities and from the business life as well as from voluntary rescue organizations will be invited onto our Delphi panel. The aim of this paper is to evaluate which kind of organizations and which kind of expertise would be the most valuable for our Delphi study, the objective of which is to improve the interoperability of organizations’ management and communications systems in emergency situations.
2012 Proceedings of PICMET '12: Technology Management for Emerging Technologies